2017
DOI: 10.1159/000453112
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Foveal Avascular Zone Area Measurements Using AngioPlex Spectral Domain Optical Coherence Tomography Angiography in Healthy Subjects

Abstract: Purpose: The aim of this study was to evaluate the repeatability and reproducibility of foveal avascular zone (FAZ) area measurements using AngioPlex spectral domain optical coherence tomography (OCT) angiography in normal subjects. Methods: Twenty-two healthy subjects (25 eyes) underwent FAZ area measurements with AngioPlex OCT. Each volunteer was separately examined 3 consecutive times by the 2 experienced observers. The FAZ area was measured using ImageJ software. Intraobserver repeatability was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
(22 reference statements)
3
35
0
2
Order By: Relevance
“…51 A recent study found that the FAZ area was~0.373 to 0.377 mm 2 in normal eyes with ICCs >0.9. 45 In the present study, the mean FAZ area was 0.467 mm 2 , 0.393 mm 2 , and 0.383 mm 2 for the CVFþ, CVFÀ, and normal groups, respectively. The area of the fovea in normal eyes is~0.785 mm 2 , and the area of the fovea should, therefore, be large enough to contain the FAZ border.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…51 A recent study found that the FAZ area was~0.373 to 0.377 mm 2 in normal eyes with ICCs >0.9. 45 In the present study, the mean FAZ area was 0.467 mm 2 , 0.393 mm 2 , and 0.383 mm 2 for the CVFþ, CVFÀ, and normal groups, respectively. The area of the fovea in normal eyes is~0.785 mm 2 , and the area of the fovea should, therefore, be large enough to contain the FAZ border.…”
Section: Discussionsupporting
confidence: 47%
“…34 In addition, intra-rater repeatability analysis was performed using repeatability coefficient and measurement error, as in previous studies. 34,[43][44][45] Repeatability coefficient was calculated as 2.77*average within-subject standard deviation (r w ), and measurement error was calculated as 1.96*r w . 34 The 95% confidence intervals of repeatability coefficient were calculated as 1:96Ãrw=…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macular quantitative parameters vary across different instruments and techniques (i.e., manual versus automatic assessment); however, several studies demonstrated that they have a good inter-and intraoperator reliability in case of same machine, acquisition and postprocessing protocols. [7][8][9]11,12,23 Measurement at the superficial plexus is highly reliable, while manual demarcation at the deep plexus may be not easy due to less definite contours.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the repeatability of OCTA measurements in the normal eye, but studies seem insufficient regarding the repeatability in patients with retinal diseases. [6][7][8][9][10][11] Therefore, in the present study, we determined the repeatability of VD measurements using OCTA in patients with diabetic macular oedema (DME), retinal vein occlusion (RVO) with macular oedema, epiretinal membrane (ERM) and wet age-related macular degeneration (AMD), which are relatively common in clinical field, and identified factors affecting the repeatability of these measurement.…”
Section: Introductionmentioning
confidence: 99%